2013
DOI: 10.1002/hbm.22281
|View full text |Cite
|
Sign up to set email alerts
|

Top‐down and bottom‐up influences on the left ventral occipito‐temporal cortex during visual word recognition: An analysis of effective connectivity

Abstract: The functional role of the left ventral occipito-temporal cortex (vOT) in visual word processing has been studied extensively. A prominent observation is higher activation for unfamiliar but pronounceable letter strings compared to regular words in this region. Some functional accounts have interpreted this finding as driven by top-down influences (e.g., Dehaene and Cohen [2011]: Trends Cogn Sci 15:254-262; Price and Devlin [2011]: Trends Cogn Sci 15:246-253), while others have suggested a difference in bottom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 49 publications
(127 reference statements)
2
41
0
Order By: Relevance
“…During word recognition, in contrast, Jacobs and Grainger (1992) found that lowering the top-down excitation from the orthographic word layer does equally well account for human performance. When testing this hypothesis by connectivity analyses of brain regions, several dynamical causal modeling (DCM; Friston et al, 2003) studies show that the bottom-up excitation of the fusiform gyrus is stronger than its top-down excitation during word recognition (Richardson et al, 2011;Schurz et al, 2014). Therefore, they support the initial proposal of Jacobs and Grainger (1992), which was based on IAM simulations of behavioral data.…”
Section: Functional Neurobiological and Phenomenological Analyses Ofmentioning
confidence: 61%
“…During word recognition, in contrast, Jacobs and Grainger (1992) found that lowering the top-down excitation from the orthographic word layer does equally well account for human performance. When testing this hypothesis by connectivity analyses of brain regions, several dynamical causal modeling (DCM; Friston et al, 2003) studies show that the bottom-up excitation of the fusiform gyrus is stronger than its top-down excitation during word recognition (Richardson et al, 2011;Schurz et al, 2014). Therefore, they support the initial proposal of Jacobs and Grainger (1992), which was based on IAM simulations of behavioral data.…”
Section: Functional Neurobiological and Phenomenological Analyses Ofmentioning
confidence: 61%
“…This particular study also showed a positive correlation in brain activity between these two areas (the IFC and VWFA). Indeed, there is evidence for anatomical and functional connectivity between the VWFA and the IFG (Bitan et al, 2006; Koyama et al, 2010, 2011; Mechelli et al, 2005; Schurz et al, 2013), suggesting that tuning in these areas may be due to the neuronal connection between these two areas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their ROI analysis revealed the same pattern (pseudoword > word activation) along the entire left vOT. Studies with German speaking adolescents and adults, which incorporated the same phonological lexical decision task, also found greater activation for pseudohomophones as compared to words in the left anterior FG (MNI: x,y,z = -45,-48,-15/-18) (Kronbichler et al, 2007; Schurz et al, 2014). This effect was interpreted as indicating an increased demand on lexical search in this region for pseudohomophones.…”
Section: Introductionmentioning
confidence: 90%